Efecto del horario de medición, posición y porción de la hoja en los índices de clorofila en la papa - de Lima Vasconcelos, Ricardo [UNESP]; de Mello Prado, Renato [UNESP]; Reyes Hernández, Alfredo; Caione, Gustavo [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2014)
The indirect measurement of chlorophyll is a diagnostic method of nitrogen in plants and its accuracy can be influenced by hour at which the reading is taken, the position of the leaflets in the plant and the portion where it is done on the leaflet reading. The objective was to evaluate the effect of hour reading, the position of the terminal leaflet on the leaf and the portion of the leaflet in the indirect of estimation of chlorophyll content index (CCI) with the use of chlorophyll meter. The experiment was performed with the cultivation of potato (S. tuberosum L.), Agate variety in the county of Ituverava São Paulo state, Brazil and consisted of 27 treatments in a factorial scheme 3 x 3 x 3 with four replications of 16 plant each, with a random distribution. The treatments were: three assessment times (08:00 am, 12:00 pm and 4:00 p.m.), three positions of leaflets on leafs (third, fourth and fifth) and three portions of the leaflet (basal, middle and distal). The evaluation of the CCI in the leaves of potato plants should be done in the leaflets of the third and fourth branch from top to bottom, regardless of the portion used leaflets, the 8:00 a.m. hours and 60 days after planting the crop. Indirect quantification of chlorophyll is a reliable tool and with potential to guide management of nitrogen fertilizer for crop.
Effect of horary measurement, position and portion of leaf in the of chlorophyll in potato index
Keywords: Alternative nutritional diagnosis; Chlorrophyll meter; Nitrogen; Solanum tuberosum L.